Inter-Observer Variation in Delineating the Pharyngeal Constrictor Muscle as Organ at Risk in Radiotherapy for Head and Neck Cancer - Petkar, Imran; McQuaid, Dualta; Dunlop, Alex; Tyler, Justine; Hall, Emma; Nutting, Chris (Frontiers in Oncology, 2021)
Abstract: Background and purpose To evaluate the inter-observer variation (IOV) in pharyngeal constrictor muscle (PCM) contouring, and resultant impact on dosimetry and estimated toxicity, as part of the pre-trial radiotherapy trial quality assurance (RTQA) within DARS, a multicentre phase III randomised controlled trial investigating the functional benefits of dysphagia-optimised intensity-modulated radiotherapy (Do-IMRT) in pharyngeal cancers. Methods and materials Outlining accuracy of 15 clinicians’ superior and middle PCM (SMPCM) and inferior PCM (IPCM) were retrospectively assessed against gold standards (GS) using volume, location, and conformity indices (CIs) on a pre-trial benchmark case of oropharyngeal cancer. The influence of delineation variability on dose delivered to the constrictor muscles with Do-IMRT and resultant normal tissue complication probability (NTCP) for physician-scored radiation-associated dysphagia at 6 months was evaluated. Results For GS, SMPCM and IPCM volumes were 13.51 cm3 and 1.67 cm3; corresponding clinician mean volumes were 12.18 cm3 (SD 3.0) and 2.40 cm3 (SD 0.9) respectively. High IOV in SMPCM and IPCM delineation was observed by the low DICE similarity coefficient value, along with high geographical miss index and discordance index values. Delineation variability did not significantly affect the mean dose delivered to the constrictors, relative to the GS plan. Mean clinician NTCP was 24.6 % (SD 0.6), compared to the GS-NTCP of 24.7%. Conclusions Results from this benchmark case demonstrate that inaccurate PCM delineation existed, even with protocol guidelines. This did not impact on delivered dose to this structure with Do-IMRT, or on estimated swallowing toxicity, in this single benchmark case.